A Multivariate Regression Analysis of Digital Pedagogy and Critical Thinking Skills in Higher Education - Siregar, Torang (Annals of Mathematics and Physics, 2026)
Background: The integration of digital pedagogy into higher education has become ubiquitous, yet its specific influence on the development of students’ critical thinking skills remains an area requiring rigorous quantitative investigation. This study aims to model the relationship between the utilization of digital pedagogical tools and the critical thinking abilities of university students. Methods: A survey instrument was developed and administered to 450 undergraduate students across three faculties. Principal Component Analysis (PCA) was employed to reduce the dimensionality of the survey data, extracting the key latent factors representing digital pedagogy. Subsequently, a multivariate linear regression model was constructed, and the least squares method was applied to estimate parameters, quantifying the linear relationship between the identified digital pedagogy components and students’ critical thinking scores. Results: PCA revealed four principal components of digital pedagogy: "Interactive Multimedia Engagement," "Asynchronous Discussion Forums," "Collaborative Online Projects," and "Adaptive Learning Technologies." These four factors explained a cumulative variance of 82.47%. The mean critical thinking score was 72.4 (SD = 8.9), with a range of 45 points, indicating significant variation among students. The multiple regression model was significant (F(4, 445) = 42.16, p < 0.001), with an R² of 0.721. All four digital pedagogy components were significant positive predictors of critical thinking skills (p < 0.01 for all). Conclusions: The study provides strong empirical evidence that specific dimensions of digital pedagogy are significantly and positively correlated with students’ critical thinking skills. The derived regression model offers a predictive framework for educators and institutions seeking to optimize digital learning environments to foster higher-order cognitive abilities.